(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
TVET institutions are expected to produce the bulk of Kenya’s middle level manpower equipped with skills to drive the attainment of infrastructural objectives of Kenya Vision 2030. However inadequate training resources brought about by poor management practices continue to impede efforts to equip Kenyan youth with employable technical skills. A programme to re-equip the institutions has been effected but it requires maintenance practices to be aligned with the new acquisitions to ensure they are constantly available for training. A survey was conducted through a questionnaire to engineering departments to evaluate compliance with maintenance performance indicators (PIs); a 5-point rating scale was used to score responses in the questionnaire that returned a combined Maintenance Management System Effectiveness Index of 0.517. This indicated a need for improvement of maintenance practices. The Analytical Hierarchical Process (AHP) method was applied which identified predictive maintenance policy as the best one to apply